Opening complete band gaps in two dimensional locally resonant phononic crystals. (May 2018) - Zhou, Xiaoling; Wang, Longqi
Abstract: Locally resonant phononic crystals (LRPCs) which have low frequency band gaps attract a growing attention in both scientific and engineering field recently. Wide complete locally resonant band gaps are the goal for researchers. In this paper, complete band gaps are achieved by carefully designing the geometrical properties of the inclusions in two dimensional LRPCs. The band structures and mechanisms of different types of models are investigated by the finite element method. The translational vibration patterns in both the in-plane and out-of-plane directions contribute to the full band gaps. The frequency response of the finite periodic structures demonstrate the attenuation effects in the complete band gaps. Moreover, it is found that the complete band gaps can be further widened and lowered by increasing the height of the inclusions. The tunable properties by changing the geometrical parameters provide a good way to open wide locally resonant band gaps. Highlights: Complete band gaps are achieved in two dimensional LRPCs. Band structures and eigen modes are studied by FEM. The translational vibrations in all directions contribute to the complete band gaps. The transmission spectra demonstrate the attenuation in the complete band gaps. Complete band gaps can be widened and lowered by tuning the height of inclusions.